THE SUBJECT "FUNDS OF COLOR AND COMPOSITION" IS ONE OF THE IMPORTANT THINGS OF FINE ART EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
Concepts of the basic laws of painting and composition, types, place and importance of painting in artistic decoration, rules and laws in the interpretation of graphic images are given and interpreted.